The IASLC Mesothelioma Staging Project: Proposals for Revisions of the N Descriptors in the Forthcoming Eighth Edition of the TNM Classification for Pleural Mesothelioma. Issue 12 (December 2016) - Rice, David; Chansky, Kari; Nowak, Anna; Pass, Harvey; Kindler, Hedy; Shemanski, Lynn; Opitz, Isabelle; Call, Sergi; Hasegawa, Seiki; Kernstine, Kemp; Atinkaya, Cansel; Rea, Federico; et al.
ABSTRACT : Introduction: : Nodal categories for malignant pleural mesothelioma are derived from the lung cancer staging system and have not been adequately validated. The International Association for the Study of Lung Cancer developed a multinational database to generate evidence‐based recommendations to inform the eighth edition of the TNM classification of malignant pleural mesothelioma. Methods: : Data from 29 centers were entered prospectively (n = 1566) or by transfer of retrospective data (n = 1953). Survival according to the seventh edition N categories was evaluated using Kaplan‐Meier survival curves and Cox proportional hazards regression analysis. Survival was measured from the date of diagnosis. Results: : There were 2432 analyzable cases: 1603 had clinical (c) staging, 1614 had pathologic (p) staging, and 785 had both. For clinically staged tumors there was no separation in Kaplan‐Meier curves between cN0, cN1 or cN2 (cN1 versus cN0 hazard ratio [HR] = 1.06, p = 0.77 and cN2 versus cN1 HR = 1.04, p = 0.85). For pathologically staged tumors, patients with pN1 or pN2 tumors had worse survival than those with pN0 tumors (HR = 1.51, p < 0.0001) but no survival difference was noted between those with pN1 and pN2 tumors (HR = 0.99, p = 0.99). Patients with both pN1 and pN2 nodal involvement had poorer survival than those with pN2 tumors only (HR = 1.60, p = 0.007) or pN0 tumors (HR = 1.62, p < 0.0001). Conclusions: : A recommendation to collapse both clinical and pN1 and pN2 categories into a single N category comprising ipsilateral, intrathoracic nodal metastases (N1) will be made for the eighth edition staging system. Nodes previously categorized as N3 will be reclassified as N2.